Auditory Predictions and Prediction Errors in Response to Self-Initiated Vowels - Knolle, Franziska; Schwartze, Michael; Schröger, Erich; Kotz, Sonja A. (Frontiers in Neuroscience, 2019)
It has been suggested that speech production is accomplished by an internal forward model, reducing processing activity directed to self-produced speech in the auditory cortex. The current study uses an established N1-suppression paradigm comparing self- and externally-initiated natural speech sounds to answer two questions: (1) Are forward predictions generated to process complex speech sounds, such as vowels, initiated via a button press? (2) Are prediction errors regarding self-initiated deviant vowels reflected in the corresponding ERP components? Results confirm an N1-suppression in response to self-initiated speech sounds. Furthermore, our results suggest that predictions leading to the N1-suppression effect are specific, as self-initiated deviant vowels do not elicit an N1-suppression effect. Rather, self-initiated deviant vowels elicit an enhanced N2b and P3a compared to externally-generated deviants, externally-generated standard, or self-initiated standards, again confirming prediction specificity. Results show that prediction errors are salient in self-initiated auditory speech sounds, which may lead to more efficient error correction in speech production.